1999
DOI: 10.1177/088307389901400706
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Pregnancy Loss, Perinatal Mortality, and Postneonatal Childhood Deaths in Families of Girls With Rett Syndrome

Abstract: Rett syndrome is a neurodevelopmental disorder that occurs predominantly in girls and results in severe physical and intellectual handicap. A popular genetic mechanism is an X-linked dominant disorder, lethal in males. A case control study design was used to investigate fetal wastage as indicated by reported miscarriage and stillbirth prevalence, and the prevalence and cause of reported neonatal and other childhood deaths. There was no disturbance in the sibling sex ratio when case and control families were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Moreover, several studies have shown no increase in parental age, 18,19 or in spontaneous abortions rate among sibs. 20,21 It is not surprising, because such skewed sex ratio might be expected only when the mother is a healthy carrier of the MECP2 mutation (perhaps spared by a skewed, favourable pattern of X inactivation) or bears the mutation in a mosaic state. Moreover, the sex limited expression of Rett syndrome is not complete.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies have shown no increase in parental age, 18,19 or in spontaneous abortions rate among sibs. 20,21 It is not surprising, because such skewed sex ratio might be expected only when the mother is a healthy carrier of the MECP2 mutation (perhaps spared by a skewed, favourable pattern of X inactivation) or bears the mutation in a mosaic state. Moreover, the sex limited expression of Rett syndrome is not complete.…”
Section: Discussionmentioning
confidence: 99%
“…Generalised estimating equations that take into account the correlation between family members can then be used for this purpose. 29 Our study, using the methods described, has been a first attempt to identify patterns of perinatal death 47 and familial aggregation 48 in families of girls with Rett syndrome. It systematically collected data from a whole juvenile population and compared results with a control group.…”
Section: Discussionmentioning
confidence: 99%
“… 3 Three families were described in which sudden infant death syndrome deaths had occurred in other siblings. 12 In a North American survey of Rett syndrome, 13 43% of extended families had a child with an intellectual disability and Down syndrome was stated as one of the most frequent presentations. As the most common known cause of intellectual disability 14 this might be expected.…”
Section: Discussionmentioning
confidence: 99%